Urolithin Metabotypes Can Determine the Modulation of Gut Microbiota in Healthy Individuals by Tracking Walnuts Consumption over Three Days - García-Mantrana, Izaskun (Nutrients, 2019)
Walnuts are rich in polyphenols ellagitannins, modulate gut microbiota (GM), and exert health benefits after long-term consumption. The metabolism of ellagitannins to urolithins via GM depends on urolithin metabotypes (UM-A, -B, or -0), which have been reported to predict host responsiveness to a polyphenol-rich intervention. This study aims to assess whether UMs were associated with differential GM modulation after short-term walnut consumption. In this study, 27 healthy individuals consumed 33 g of peeled raw walnuts over three days. GM profiling was determined using 16S rRNA illumina sequencing and specific real-time quantitative polymerase chain reactions (qPCRs), as well as microbial activity using short-chain fatty acids analysis in stool samples. UMs stratification of volunteers was assessed using ultra performance liquid chromatography–electro spray ionization–quadrupole time of flight–mass spectrometry (UPLC-ESI-QTOF-MS) analysis of urolithins in urine samples. The gut microbiota associated with UM-B was more sensitive to the walnut intervention. Blautia, Bifidobacterium, and members of the Coriobacteriaceae family, including Gordonibacter, increased exclusively in UM-B subjects, while some members of the Lachnospiraceae family decreased in UM-A individuals. Coprococcus and Collinsella increased in both UMs and higher acetate and propionate production resulted after walnuts intake. Our results show that walnuts consumption after only three days modulates GM in a urolithin metabotype-depending manner and increases the production of short-chain fatty acids (SCFA).